Lymphocytic chalones under stress conditions - Garkava, K. G. (Problems of Environmental Biotechnology, 2014)
It was shown that the production and activity of lymphocytic chalones - inhibitors of lymphocyte proliferation when exposed to stress factors was depended on the nature of stress factors, dose and timing of their actions.